Concatenated RS-convolutional codes for MIMO-OFDM system - Hussain, Ghasan Ali; Mokhtar, Makhfudzah; Raja Abdullah, Raja Syamsul Azmir (Knowledgia Review, Malaysia, 2011)
In this study, the performance of multi input multi output of orthogonal frequency division multiplexing system will be investigate by using channel coding of concatenated Reed-Solomon with convolutional codes. The system has been tested over additive white Gaussian noise with both of Rayleigh and Rician fading channels. The aim of proposing the concatenated Reed Solomon/convolutional codes is to improve the signal to noise ratio of the orthogonal frequency division multiplexing system. The simulation results shown a significant improvement achieved to the multiple input multiple output of orthogonal frequency division multiplexing system by using concatenated technique against other techniques. The coding gain achieved in the proposed technique was 10 dB at the BER of 10-2 compared to the uncoded system over Rayleigh fading with additive white Gaussian noise while it was almost 7 dB at 10-2 over Rician fading channel with additive white Gaussian noise. The results showed that, the degradation in the performance of orthogonal frequency division multiplexing system due to Rayleigh fading channel was more than the Rician fading channel. Lastly, the simulation results proved that by using concatenated Reed Solomon/convolutional codes with multiple input multiple output system will achieve more improvement than by using only concatenated Reed Solomon/Convolutional codes with orthogonal frequency division multiplexing system.